Identification of deposits from modern and ancient large tsunamis by means of environmental DNA - Tetsuya Shinozaki; Akira Iguchi; Miyuki Nishijima; Kazuhisa Goto; Shigehiro Fujino (Scientific Reports)
Abstract We examined the potential of environmental DNA (eDNA) for identifying tsunami deposits in the geological record using lake-bottom sediments in the Tohoku region, Japan. The presence of eDNA from marine organisms in a lacustrine event deposit provides very strong evidence that the deposit was formed by an influx of water from the ocean. The diverse DNA assemblage in the deposit formed by the 2011 Tohoku-oki tsunami included DNA of marine origin indicating that eDNA has potential as an identifying proxy for tsunami deposits. Subsequently, we examined the applicability of eDNA for recognizing paleo-tsunami events using the deposits formed by the 869 CE Jogan tsunami and a prehistoric event (2400–2900 cal year BP). The taxa detected in the tsunami deposits were markedly different from those of the background sediments. Many taxa that were represented in the Jogan tsunami deposit were also detected in the layer immediately above the tsunami deposit. This layer was indistinguishable from the overlying peat by visual observation, but the eDNA results suggest that it is likely to be a muddy tsunami deposit. The results of this study indicate that eDNA has the potential to elucidate the origin of event deposits that have been difficult to identify.